Geometry of the Altenberg-Teplice Caldera revealed by the borehole and seismic data in its Czech part - Mlcoch,B.; Skacelova,Z. (Journal of Geosciences, 2010)
The Altenberg-Teplice Caldera (ATC) in the eastern Krusne hory Mts./Erzgebirge (Czech Republic, Germany) is the largest centre of Late Palaeozoic acid volcanism in the Bohemian Massif. Previous studies were focused mainly on its exposed part in the north, as the southern part is covered by Tertiary sediments. Borehole data, geological mapping and geophysical survey enabled to gain a new image of its areal and vertical extent and to construct a digital model of individual geological units. The evaluation of the Czech Geological Survey - Geofond borehole database and 3D modelling of the crystalline relief and of the rhyolite complex enabled to reconstruct the geometry of the Czech part of the ATC.
Keywords: Saxothuringian Zone; Eastern Krusne hory Mts.; Erzgebirge Volcano-Plutonic Complex; Altenberg-Teplice Caldera; borehole; seismic data; erosion level